Modeling and Analysis of the Fluorescent Lamp Energy Parameters - Otas, K.; Vaskys, A. (Elektronika ir Elektrotechnika, 1999)
The mathematical model of the fluorescent lamp was improved so that it would be possible to calculate 254 nm wavelength resonance illumination flux of mercury vapor. Using this improved model linked up with ESACAP software program, fluorescent lamp energy parameters were analysed. The lamp was fed with AC of 50 and 1000 Hz. The current was stabilized with three types of ballasts. Such energy parameters as resonance illumination flux of mercury vapor, power of plasma column and plasma column illumination efficacy were investigated. The influence of the various factors to energy characteristics was analysed.